Understanding health knowledge failures: uncertainty versus misinformation - Peter J. Schulz; Kent Nakamoto (Scientific Reports)
Abstract Studies of health literacy often employ knowledge measures and typically focus on the correct answers as reflections of the level of (accurate) knowledge and literacy. The wrong answers are treated as failures but usually without further consideration. This paper argues for the importance of distinguishing two forms of knowledge failure—being uninformed(uncertain about information) and being misinformed(believing objectively wrong information)—because of their differing effects on communication responses and associated judgments and decisions. A measure is developed from the incorrect answers indicating error due to uncertainty versus error due to misinformation. In a survey of a representative sample survey of Swiss adults, the uninformed are more likely than the misinformed to hold positive beliefs and attitudes toward vaccination, recommend them to others, and received more vaccinations themselves. The effects are distinguished from those of objective knowledge and suggest that the misinformed form a distinctive group. The importance of separately measuring and understanding knowledge failures to consumer judgement, decision, and welfare are discussed.